The Central-European small town - Pirisi, Gábor (Revija za geografijo, 2025)
Small towns are long-term stable elements of the urban network with established residential and service roles. Geographical research has often neglected them, and accordingly, certain conceptual issues require clarification. However, particularly in countries with low urbanisation, small towns play a significant role in the transformation and modernisation of rural areas. Nevertheless, the increasingly global scale of economic and social processes poses a considerable challenge to their traditional functions, reshaping their development framework. In this evolving context, the flexible adaptive capacity of small towns - defined as resilinece - becomes crucial. Alongside addressing globalisation challenges, this study outlines a cognitive resilience model that could also serve as the basis for a new planning practice.
Keywords: Globalizacija; Mala mesta; odpornost; reindustrialisation; reindustrializacija; resilience